Difference of Maternal Parenting Style on Child’s Growth And Motoric Development (Public Health Perspective Journal, 2019)
The indicators for determining the health of infants are through their nutritional status. Developmental disorders of the toddler include gross movement disorders, subtle movements, socialization, independence and development of speech and language. The mother plays a role as an educator and care giver to their family. Other condition shoews that some women work to meet family needs and develop her abilities. The integtated Community Health Center of Gribig in Kudus Regency is dominated an industrial area where the number of malnourished children under five years of age each year increases, namely 3 cases in 2016 and 4 cases in 2017. And the motoric development experienced delays is not appropriate at his age. The purpose of the study was to determine the ratio of parenting style of working mother and housewife towards the growth and motor skills of children under five. This research was a quantitative research, with a cross sectional approach. The research sample was 90 respondents with Propotionate stratified random sampling technique. The instrument used observation sheets and questionnaires. Data collection techniques were interviews and observations. The results of the analysis used chi square test which is obtained parenting style in working mothers with toddler growth p = 0.026, while parenting style in housewife towards toddler growth p = 0.047, parenting style of working mothers with toddlers motorized are p = 0.001, parenting style of housewife with toddlers’ motor is p = 0.003 so that there is no difference of maternal parenting style on child’s growth and motoric development.